Գարեգին եպս. Սրուանձտեանցի թատերգութիւնները - Վարդանեան, Լուսինէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Епископ Гарегин Срвандзтянц вошел в мир литературы двумя пьесами — «Трагедия Великого Саака Партева и падение Арташира Аршакуни» (1860— 70 гг.) и «Шушан Шаваршана» (1875 г.). Мотивом для написания пьес послужило восстание в Зейтуне в 1862 году, и было взято за основу Срвандзтянцем, который выступал с публикациями на страницах «Арцви Васпуракан» («Орел Васпуракана»), вдохновляя борющихся. Его призывы к армянской молодежи были направлены на объединение нации, сплочение и единение, что особенно отражено в первом произведении — «Трагедия Великого Саака Партева…». «Шушан Шаваршана» является авторским произведением с ярко выраженной авторской позицией, в котором Срвандзтянц, как читатель, видит мир через призму любимой книги — «О Вардане и войне армянской» Егише. Посредством этого произведения он представляет и объясняет соединенные с национальными чувствами личные переживания. Этим своим произведением писатель передает послание, дошедшее с V века, которое продолжает передаваться и далее. Данное аналитическое изложение является попыткой проследить за указанными темами. Bishop Karekin Srvandztiants entered the world of literature with two plays: “Tragedy of Sahak the Great Parthian and the Fall of Ardashir Arshakuni” (1860— 70s) and “Shushan Shavarshana” (1875). The motivation for writing the plays was the Zeytun uprising in 1862 that inspired Srvandztiants, whose articles on the pages of “Eagle of Vaspurakan” were encouraging the fighters. His appeals to the Armenian youth were aimed at uniting the nation, making it undivided and unanimous, which is especially reflected in the first play “Tragedy of Sahak the Great Parthian and the Fall of Ardashir Arshakuni”. “Shushan Shavarshana” is a work completely inseparable from the author’s self, in which the reader Srvandztiants sees the world through the truth revealed by his favorite book “On Vardan and the Armenian War” by Yeghishe; explains his personal experience assimilated into national sentiments through the sacred meaning that book had for him. With this work, the writer conveys the message that was transmitted from the original to the original from the fifth century to his days and perhaps to coming generations. This analytical essay is an attempt to observe all this.
Keywords: Պատմութիւն; Բանասիրութիւն; Թատերգութիւն